IOP-lowering therapy and ocular surface in glaucoma. Part 1. The effects of drug substances of glaucoma medications on the ocular surface - A.V. Antonova; V.P. Nikolaenko; V.V. Brzheskiy (РМЖ "Клиническая офтальмология")
A.V. Antonova1, V.P. Nikolaenko1,2, V.V. Brzheskiy3 1City Multidisciplinary Hospital No. 2, St. Petersburg, Russian Federation 2St. Petersburg State University, St. Petersburg, Russian Federation 3St. Petersburg State Pediatric Medical University, St. Petersburg, Russian Federation This article reviews recent data on the effect of active ingredients and preservatives of IOP-lowering medications on the ocular surface. The rate and severity of ocular surface disease depend on the intensity and duration of glaucoma treatment as well as baseline ocular surface status. In addition, each class of IOP-lowering medications is characterized by specific effects on ocular surface. Long-term pharmacotherapy results in tear film instability and tear hyperosmolarity. Dose- and exposition-dependent loss of goblet cells, corneal epithelial toxicity, meibomian gland dysfunction, increased activity and expansion of fibroblasts, and pro-inflammatory cytokine release from goblet cells account for the development and progression of symptoms and signs of dry eye as demonstrated by progressive deterioration in Ocular Surface Disease Index (OSDI), Norn’s test, and Schirmer’s test. The result is poor adherence to medical treatment and poor outcomes  of conjunctival glaucoma surgery.  Our findings can be applied to develop perioperative management strategy of patients with glaucoma to maximize the chances of long-term surgical success. Keywords: glaucoma, IOP-lowering treatment, ocular surface, dry eye disease, Ocular Surface Disease Index, inflammation, preservatives, benzalkonium chloride, preservative-free medication. For citation: Antonova A.V., Nikolaenko V.P., Brzheskiy V.V. IOP-lowering therapy and ocular surface in glaucoma. Part 1. The effects of drug substances of glaucoma medications on the ocular surface. Russian Journal of Clinical Ophthalmology. 2020;20(2):79–84. DOI: 10.32364/2311-7729-2020-20-2-79-84.